Collaborative Learning on BEEd Students’ Mastery of Mathematical Reasoning: Basis for Developing an Intervention Program - Mary Jane G. Bolaños; Jonel S. Cerbito (Researchparks Publishing, 2026)
This study examined the effect of collaborative learning on Bachelor of Elementary Education (BEEd) students’ mastery of mathematical reasoning and provided a basis for the development of an intervention program. Employing a one-group pretest–posttest quasi- experimental design, the study involved 134 first-year BEEd students from the University of Cabuyao. The intervention incorporated structured collaborative learning approaches, including constructivist, collaborative, inquiry-based, integrative, and reflective strategies within mathematics instruction. Results indicated that collaborative learning practices were implemented to a very high extent across all dimensions. Inferential statistics revealed statistically significant gains in students’ mathematical reasoning following the intervention, particularly in problem understanding, logical reasoning, application of mathematical concepts, and accuracy of solutions, as determined through the Wilcoxon Signed Ranks Test. Regression analysis further demonstrated that integrative and reflective approaches significantly predicted specific reasoning domains, highlighting their differential contributions to higher-order cognitive processes. The findings affirm the effectiveness of collaborative learning as a student-centered pedagogical framework that enhances mathematical reasoning. The study underscores the importance of integrative and reflective strategies in fostering deep conceptual understanding and cognitive engagement. An evidence-based intervention program is proposed to strengthen mathematical reasoning and inform instructional practices in teacher education, contributing to the preparation of competent, reflective, and future-ready educators.